Effective search for potentially innovative scientific results in medicine - M. B. Khrustalev; A. A. Maksimova (IRBIS LLC, 2019)
Medicine is one of the most important and rapidly developing branches of science. Research and developments projects run by scientific organizations and universities in this field are ultimately aimed at preserving the public health; these projects are expected to be rapidly implemented and become available to consumers. Yet in the area of medicine, the process of implementation can take many years. There is a gap between the developers (scientific organization, university), investors, and manufacturers due to the difficulty in assessing the innovation potential of the scientific results in medicine. The aim of this study was to determine the inclusion criteria for research conducted in medical universities to be incorporated in the innovation process; such criteria were supposed to be based on other (indirect) indicators ranking the medical universities. Material and methods. The study included twenty medical universities in Russia, largest in terms of the scientific and teaching staff. These universities were ranked according to the number of citations in the Web of Science over the period 2013-2017. Also, using the SciVal module developed by Elsevier, the number of publications with the participation of industrial partners was estimated. The assessment of the invention activity of medical universities was found in the materials published by the Russian Analytical Center "Expert". Results. According to the scientometric analysis, medical universities with the most promising scientific products and scientific developments, have been in low demand by Russian and foreign companies. Conclusion. Due to the low activity of medical universities in implementing their intellectual production, potential investors and manufacturers should pay more attention to those medical universities, which produce a greater number of high-quality scientific results.